2019
DOI: 10.1002/2211-5463.12690
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of CDR3 regions in paired human αβ CD8 T cells

Abstract: The majority of human CD8 cytotoxic T lymphocytes express αβ T‐cell receptors that recognize peptide–MHC class I complexes. Considerable attention has been devoted to TCR β repertoires, but study of TCR α chains has been limited. To gain a better understanding of the features of CDR3α and CDR3β in paired samples, we comprehensively analyzed 776 unique paired αβ TCR CDR3 regions in this study. We found that (I) the CDR3 length among paired αβ TCRs had a fairly narrow distribution due to random assortment of CDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Additionally, a characterization of structure and dynamics of a TCR is essential to elucidate the antigen-binding mechanism, the involved conformational changes and the associated biological implications ( 4 , 17 , 18 ). X-ray studies comparing TCRs crystallized with and without the pMHC complex revealed a high flexibility in the binding interface ( 1 , 3 , 14 , 17 , 20 ). However, crystal structures represent only a snapshot of a specific protein conformation that can be distorted due to crystal packing effects ( 15 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a characterization of structure and dynamics of a TCR is essential to elucidate the antigen-binding mechanism, the involved conformational changes and the associated biological implications ( 4 , 17 , 18 ). X-ray studies comparing TCRs crystallized with and without the pMHC complex revealed a high flexibility in the binding interface ( 1 , 3 , 14 , 17 , 20 ). However, crystal structures represent only a snapshot of a specific protein conformation that can be distorted due to crystal packing effects ( 15 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…A possible assignment of the crystal structures to kinetic macrostates in solution is shown in Figure 6 for the CDR3ß loop. Various studies focused on characterizing the role of the CDR3 loops and identified strong structural loop correlations in the peptide recognition process ( 13 , 14 , 19 ). As evidence for a structural correlation of the CDR3 loops has been provided, we reconstructed thermodynamics and kinetics for the combined CDR3 loops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the AAs with a higher frequency in all NCs were threonine and tyrosine, which are both polar hydrophilic residues. Apart from NCs, a general trend that was recorded regarding the most frequent clonotypes post-RT was the enrichment of CDR3 with polar and/or acidic AAs, which has been found to contribute to the TCR bonding process and may be related to the restricted localization of TCR on HLA-A2 ( 25 ). Notably, it has previously been shown that the nature of AA residues (especially at position 109) within the CDR3 has a crucial role for T-cell autoreactivity, which increases significantly in the presence of hydrophobic residues ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of negative charges in the TCR binding loop, especially the germline loop encoded by the TCRVα and Vβ genes, enables this to occur and is related to the restricted localization of TCR on HLA-A2 (73). Yu et al also found that the bicyclic loops of TCR α and β chains contain many charged polar residues (73). The amino acids in the CDR3 loop region located on the TCR α and β chains are significantly different, and each chain has a special role in recognizing the antigen-MHC complex.…”
Section: Discussionmentioning
confidence: 99%